Hand hygiene for the management of a patient infected with Clostridium difficile in the presence of hospital infections - Krystyna Nowacka; Renata Flitta; Joanna Siminska; Piotr Porzych; Sebastian Grzyb; Wojciech Hagner (Kazimierz Wielki University, 2017)
With the dynamic development of medicine nosocomial infections represent a big threat not only for patients admitted to the hospital, but also for health professionals and visitors. Healthcare-associated infections are associated with an extended stay patient, complications in the healing process, and risk of loss of life and health by the patient. Nosocomial infections worldwide are legally governed by the provisions of the legislation of the Member State concerned. The first act regulating the fight against hospital infections in Poland in the institutional way in 2001, introducing "the law on infectious diseases and infections". Micro-organisms causing hospital infections are most often transmitted to the hands of the medical staff. Hygienic hand disinfection is more effective against microorganisms than hand-washing, and should be used as the method of choice before many activities related to patient care. The World Health Organization considers hand hygiene as a basic element of prevention hospital infections. Such pathogens include Clostridium difficile. That is the most important pathogen causing diarrhea.  Stem infection of Clostridium difficile may cause serious diseases and medical conditions, particularly in the elderly, debilitated as a result of chronic diseases. The need to respect the principles of hand hygiene by medical staff is widely recognized. Causes of irregularities in the field of hand hygiene are different, for example. the intensity of the work, insufficient medical knowledge, limited access to devices for effective hand hygiene or ignorance of hand disinfection techniques.